Indonesia’s 2018 Regional Elections – The Generals’ Election : More Officers in Politics, More Democracy? - Marzuki, Keoni (2018)
Several military and police generals have announced their candidacies for the 2018 simultaneous regional elections before they retire from active service. What induced these generals to enter politics and what does it portend for Indonesian democracy?